Knock‐out of N‐glycolylneuraminic acid attenuates antibody‐mediated rejection in xenogenically perfused porcine lungs. (17th October 2022) - Chaban, Ryan; Habibabady, Zahra; Hassanein, Wessam; Connolly, Margaret R.; Burdorf, Lars; Redding, Emily; Laird, Christopher; Ranek, Jolene; Braileanu, Gheorghe; Sendil, Selin; Cheng, Xiangfei; Sun, Wenji; et al.
Abstract: Background: Antibody‐mediated rejection has long been known to be one of the major organ failure mechanisms in xenotransplantation. In addition to the porcine α1, 3‐galactose (α1, 3Gal) epitope, N‐Glycolylneuraminic acid (Neu5Gc), a sialic acid, has been identified as an important porcine antigen against which most humans have pre‐formed antibodies. Here we evaluate GalTKO.hCD46 lungs with an additional cytidine monophospho‐N‐acetylneuraminic acid hydroxylase (CMAH) gene knock‐out (Neu5GcKO) in a xenogeneic ex vivo perfusion model Methods: Eleven GalTKO.hCD46.Neu5GcKO pig lungs were perfused for up to 6 h with fresh heparinized human blood. Six of them were treated with histamine (H) blocker famotidine and 1‐thromboxane synthase inhibitor Benzylimidazole (BIA) and five were left untreated. GalTKO.hCD46 lungs without Neu5GcKO ( n = 18: eight untreated and 10 BIA+H treated) served as a reference. Functional parameters, blood, and tissue samples were collected at pre‐defined time points throughout the perfusion Results: All but one Neu5GcKO organs maintained adequate blood oxygenation and "survived" until elective termination at 6 h whereas two reference lungs failed before elective termination at 4 h. Human anti‐Neu5Gc antibody serum levels decreased during the perfusion of GalTKO.hCD46 lungs by flow cytometry (∼40% IgM, 60% IgG), whereas antibody levels in Neu5GcKO lung perfusions did not fall (IgM p = .007; IgG p < .001). Thromboxane elaboration, thrombin generation, and histamine levels were significantly reduced with Neu5GcKO lungs compared to reference in the untreated groups ( p = .007, .005, and .037, respectively); treatment with BIA+H masked these changes. Activation of platelets, measured as CD62P expression on circulating platelets, was lower in Neu5GcKO experiments compared to reference lungs ( p = .023), whereas complement activation (as C3a rise in plasma) was not altered. MCP‐1 and lactotransferin level elevations were blunted in Neu5GcKO lung perfusions ( p = .007 and .032, respectively). Pulmonary vascular resistance (PVR) rise was significantly attenuated and delayed in untreated GalTKO.hCD46.Neu5GcKO lungs in comparison to the untreated GalTKO.hCD46 lungs ( p = .003) Conclusion: Additional Neu5GcKO in GalTKO.hCD46 lungs significantly reduces parameters associated with antibody‐mediated inflammation and activation of the coagulation cascade. Knock‐out of the Neu5Gc sialic acid should be beneficial to reduce innate immune antigenicity of porcine lungs in future human recipients.